A comparative study on the effectiveness of losartan/hydrochlorothiazide and telmisartan/hydrochlorothiazide in patients with hypertension. (July 2014) - Hamada, Toshihiro; Kuwabara, Masanari; Watanabe, Arisa; Mizuta, Einosuke; Ohtahara, Akira; Omodani, Hiroki; Watanabe, Masashi; Nakamura, Hiroki; Hirota, Yutaka; Miyazaki, Satoshi; Kato, Masahiko; Ogino, Kazuhide; et al.
Abstract Purpose: Long-term effects of a low-dose hydrochlorothiazide (HCTZ) with losartan (LOS) on uric acid (UA) metabolism as well as glucose metabolism have been studied in hypertensive patients in comparison with those of a low-dose HCTZ with telmisartan (TEL). Method: Fifty-nine hypertensive patients were allocated to a combination therapy with either losartan (50 mg/day)/HCTZ (12.5 mg/day) (LOS + HCTZ group: n = 37) or telmisartan (40 mg/day)/HCTZ (12.5 mg/day) (TEL + HCTZ group: n = 22), respectively. Before and 1 year after the treatment, blood pressure and biochemical parameters of blood and urine were evaluated. Results: Both systolic and diastolic blood pressures significantly decreased in two groups, without any statistical differences among them. LOS + HCTZ caused no changes in the serum UA level or the ratio of UA clearance to creatinine clearance (CUA/Ccr), whereas TEL + HCTZ significantly increased the serum UA level and reduced CUA/Ccr. LOS + HCTZ did not influence CUA/Ccr in patients with their serum UA below 5.4 mg/dl, while LOS + HCTZ significantly increased CUA/Ccr in patients with their serum UA above 5.5 mg/dl. TEL + HCTZ significantly reduced CUA/Ccr in patients with their serum UA below and above 5.4 mg/dl to increase serum UA level significantly. Neither combination therapies caused any changes in fasting plasma glucose, HbA1c and HOMA-R. In patients with their serum UA level above 5.4 mg/dl, TEL + HCTZ increased HOMA-R, whereas LOS + HCTZ did not. Conclusions: LOS + HCTZ did not influence UA metabolism as well as glucose metabolism, likely because of inhibitory action of losartan on URAT1, although TEL + HCTZ were accompanied with impairment of the UA metabolism and glucose metabolism.